Kecerdasan Buatan dan Kedaulatan Hukum: Studi Kualitatif atas Tantangan Regulasi AI dalam Bingkai Negara Hukum Indonesia - Muhammad Darwis (Bahasa Indonesia, 2026)
This research aims to empower the regulatory challenges of artificial intelligence (AI) within the framework of the Indonesian legal state. By using a qualitative approach and literature study methods as well as analysis of legal documents, this research found that the exponential development of AI has not been matched by adequate legal instruments in Indonesia. Legal uncertainty, overlapping institutional authority, and the absence of a clear juridical definition of AI are the main obstacles in realizing legal sovereignty in the digital era. This research recommends the need for harmonization of regulations and strengthening institutional capacity to respond to technological dynamics